Acidic Cannabinoids Suppress Proinflammatory Cytokine Release by Blocking Store-operated Calcium Entry. Issue 4 (8th July 2022) - Faouzi, Malika; Wakano, Clay; Monteilh-Zoller, Mahealani K; Neupane, Ram P; Starkus, John G; Neupane, Jayanti Bhandari; Cullen, Aaron J; Johnson, Brandon E; Fleig, Andrea; Penner, Reinhold
Abstract: Cannabis sativa has long been known to affect numerous biological activities. Although plant extracts, purified cannabinoids, or synthetic cannabinoid analogs have shown therapeutic potential in pain, inflammation, seizure disorders, appetite stimulation, muscle spasticity, and treatment of nausea/vomiting, the underlying mechanisms of action remain ill-defined. In this study we provide the first comprehensive overview of the effects of whole-plant Cannabis extracts and various pure cannabinoids on store-operated calcium (Ca 2+ ) entry (SOCE) in several different immune cell lines. Store-operated Ca 2+ entry is one of the most significant Ca 2+ influx mechanisms in immune cells, and it is critical for the activation of T lymphocytes, leading to the release of proinflammatory cytokines and mediating inflammation and T cell proliferation, key mechanisms for maintaining chronic pain. While the two major cannabinoids cannabidiol and trans-Δ 9 -tetrahydrocannabinol were largely ineffective in inhibiting SOCE, we report for the first time that several minor cannabinoids, mainly the carboxylic acid derivatives and particularly cannabigerolic acid, demonstrated high potency against SOCE by blocking calcium release-activated calcium currents. Moreover, we show that this inhibition of SOCE resulted in a decrease of nuclear factor of activated T-cells activation and Interleukin 2 production in human T lymphocytes. Taken together, these results indicate that cannabinoid-mediated inhibition of a proinflammatory target such as SOCE may at least partially explain the anti-inflammatory and analgesic effects of Cannabis . Graphical Abstract: